Implementation of Consumer Warranty Rights by Mobile Phone Service Business Actors Maslahah Mursalah Perspective and Law No. 8 of 1999 concerning Consumer Protection (Case Study in Gunung Tua, North Padang Lawas Regency) - Bintang Sri Bulan; Fatimah Zahara (LP2M IAIN Palopo, 2026)
This study aims to analyze the implementation of consumer warranty rights in mobile phone service services and assess its conformity with applicable legal provisions and review the practice from the perspective of maslahah mursalah. The problems studied focus on the gap between legal norms and practices in the field related to the provision of guarantees by business actors. The method used is empirical legal research with a qualitative approach through interviews and literature studies. The results of the study show that the implementation of the warranty has not been running optimally. Some business actors have provided guarantees both in writing and verbally. However, there are still business actors who have not provided any warranty This condition causes consumer rights to not be fulfilled and causes legal uncertainty. Based on Law Number 8 of 1999 concerning Consumer Protection, this practice has not fulfilled the obligations of business actors. From the perspective of maslahah mursalah, this condition does not reflect the principle of benefit because it has not been able to provide protection and prevent losses for consumers. This study concludes that the implementation of the warranty has not reflected legal certainty, justice, and optimal utility. Therefore, a mandatory policy is needed for business actors to provide guarantees to consumers as a form of responsibility for the services provided and to realize more effective consumer protection.